FEATURES OF ACCOUNTING OF COSTS IN ONLINE TRADING - I. Zakharov; Z. Korzovatykh (Вестник университета)
In the article described the peculiarities of the methodology of the costs of circulation in online trading. Due to the fact that the range of calculation cost items of treatment for the purposes of management defined by organizations in Commerce, including electronic commerce, on their own, the clauses increases the likelihood of tolerance of errors in the accounting of the costs of circulation. The authors propose a list of articles of calculation costs of circulation that will reduce the final price of the product and to make it more affordable for the buyer.